Extended phylogenetic analysis and morphology of the Iresine cassiniiformis – I. hartmanii alliance (Amaranthaceae) reveals two further geographically distinct species - Thomas Borsch; Hilda Flores-Olvera (Botan‪ical Sciences)
Background: Shrubs recognized as I. hartmanii were known from the northern Mexican deserts, whereas I. cassiniiformis is considered to occur throughout the Mexican highlands. Morphologically similar individuals were reported under both names also south beyond the Isthmus of Tehuantepec to Guatemala.